Happily never after - Painter, Lynn (Berkley Romance, 2024)
"Their name? The objectors. Their job? To break off weddings as hired. Their dilemma? They might just be in love with each other. When Sophie Steinbeck finds out just before her wedding that her fiancé has cheated yet again, she desperately wants to call it off. But because her future father-in-law is her dad's cutthroat boss, she doesn't want to be the one to do it. Her savior comes in the form of a professional objector, whose purpose is to show up at weddings and proclaim the words no couple (usually) wants to hear at their wedding: "I object!" During anti-wedding festivities that night, Sophie learns more about Max the Objector's job. It makes perfect sense to her: he saves people from wasting their lives, from hurting each other. He's a modern-day hero. And Sophie wants in. Max and Sophie start working together, the two love cynics going from wedding to wedding, and she's having more fun than she's had in ages. Sophie looks forward to every nerve-racking ceremony, where she gets to save the lovesick souls of the betrothed masses. As they spend more time together, however, they realize their physical chemistry is off the charts, leading them to dabble in a little hookup session or two--but it's totally fine because they definitely do not have feelings for each other. Love doesn't exist, after all. And then everything changes. A groom-to-be hires Sophie to object, but his fiancée is the woman who broke Max's heart. As Max wrestles with whether he can be a party to her getting hurt, Sophie grapples with the sudden realization that she may have fallen hard for her partner in crime"--